A PEGylated deep eutectic solvent for controllable solvothermal synthesis of porous NiCo2S4 for efficient oxygen evolution reaction. Issue 13 (19th May 2017) - Jiang, Jingyun; Yan, Chuanyu; Zhao, Xinhui; Luo, Hongxia; Xue, Zhimin; Mu, Tiancheng
Abstract : A PEGylated deep eutectic solvent was developed and used for one step solvothermal synthesis of NiCo2 S4 for efficient oxygen evolution reaction. Abstract : As ionic liquid analogues or quasi-ionic liquids, deep eutectic solvents (DESs) have been applied in many fields in the past few years. Herein, a novel PEGylated DES composed of PEG 200 and thiourea was formed for the first time and used for solvothermal synthesis of nickel cobalt sulfides. The structure and composition of the as-synthesized sulfides can be tuned by adjustment of the ratio of the reactants. The PEGylated DES plays multiple roles as a solvent, a shape-control agent, and a sulfur source in the synthesis of sulfides. Compared with traditional sulfuration routes, this proposed route is cost-effective and energy-efficient by combining solvothermal synthesis and the sulfuration process. The prepared sulfides were used as catalysts for electrochemical water oxidation and they exhibited excellent oxygen evolution reaction (OER) performance, especially for NiCo2 S4 with hierarchical pores. The overpotential ( η ) demand was 337 mV for the current density reaching 10 mA cm −2 and the Tafel slope was 64 mV dec −1 in an alkaline medium (1 M KOH) for NiCo2 S4 . In addition, NiCo2 S4 demonstrated long-term stability with little deactivation after either thirty hours of continuous operation or two thousand cycles and a high faradaic efficiency of 95.8%. Synergistic effects including a relatively high Brunauer–Emmett–Teller area, abundant active sites, easy diffusion of electrolytes and oxygen gas, and strong structural integrity contribute to the high activity and long-term stability of the catalyst for OER. This study provides a new method for the synthesis of hierarchically structured metal sulfides for energy conversion and storage applications.